Réponses

2013-01-02T12:28:22+01:00

a) D = (2x+3)² + (x-5) (2x+3)

D = 4x² + 12x + 9 + 2x² + 3x - 10x - 15

D = 6x² + 5x - 6

 

 b) D = (2x+3)² + (x-5) (2x+3)

D = (2x+3) [(2x+3) + (x-5)]

D = (2x+3) (2x + 3 + x -5)

D = (2x+3)(3x-2)

 

c) (2x+3)(3x-2) = 0

Je reconnais une équation produit. Or un produit est nul si l'un de ses facteurs est nul.

donc

2x+3 = 0                                             ou  3x-2 = 0

2x+3-3 = 0-3                                            3x -2 +2 = 0+2

2x / 2 = -3 / 2                                            3x / 3 = 2 / 3

x = -1,5                                                      x  = 2/3

 

Les solutions de l'éduation sont -1,5 et 2/3